The Oxford paperback Spanish dictionary: Spanish-English, English-Spanish - Christine Lea (Oxford Univ. Press, 1994)
This dictionary covers the essential vocabulary of everyday life. It composes 45000 words and phrrases, 70000 translations, up to date and easy to use, includes coverage of Latin American Spanish, pronunciation guidance, verb tables. This dictionary is specially designed for students, tourists, and travellers